Tectono-sedimentary evolution of the southwestern Tarim Basin in the cretaceous in response to basin-range coupling: New insights from basin and landscape dynamics modeling - Chang, Jia; Liu, Keyu; Yuan, Wenfang; Liu, Jianliang; Zhang, Liqiang; Chen, Cai (Palaeogeography, palaeoclimatology, palaeoecology, 2024)
The southwestern Tarim Basin in western China is one of the most dynamic areas of basin-range coupling in the Cretaceous. This study presents the first attempt to simulate the tectono-sedimentary evolution of the southwestern Tarim Basin during the Cretaceous in three dimensions using a basin and landscape dynamics modeling approach. We have simulated the evolution of the southwestern Tarim Basin and the West Kunlun Orogenic Belt (WKOB) during the Cretaceous over a period of 79 million years. Apart from numerous local fans and streams perpendicular to the mountain front, a major paleo-drainage system paralleling to WKOB was developed within the depression during the Early Cretaceous. It subsequently evolved into two drainage systems by a topographic high within the depression in the Late Cretaceous, forming two river channels flowing to the northwest and southeast, respectively. During the Cretaceous the southwestern Tarim Basin was infilled by sediments of up to 3500 m thick. WKOB contributed the bulk sediments to the basin (75.53%), whereas the Markit Slope to the north contributed 24.23%. The sedimentary centers were located mainly in the areas of the southeastern Wupoer and the northwestern Qibei structural belts. The closure of the Paleo-Tethys Ocean towards the end of Triassic around 200 Ma caused the development of paleouplifts in the region and a subsequent overlapping of the Jurassic by the Cretaceous strata. During the Cretaceous, the tectonic movement was relatively quiescent. Only the topmost sediments were subject to erosion at the end of the Cretaceous, as a result of the subduction of the Neo-Tethys Ocean to the south. Paleoclimate and/or precipitation controlled the denudation rate of the orogenic belts while tectonic subsidence controlled the thickness of sediments within the basin. This finding provides new insights for quantitatively evaluating geomorphic and landscape evolution and source-to-sink systems in the southwestern Tarim Basin. •Using Badlands to provide new insights on tectono-sedimentary evolution.•Paleoclimate and precipitation appear to have controlled the denudation rate of the orogenic belts.•Differential tectonic uplift and subsidence of the orogenic belts and depression controlled the amount of sedimentation.•The sedimentary provenances were sourced from the West Kunlun Orogenic Belt (75%) and the Markit Slope (24%).•Simulation reveals a main paleo-drainage system evolved into a two-channel river system.